Accuracy of an adherence score and time in therapeutic range among patients on chronic use of vitamin K antagonists (Research, Society and Development, 2021)
To validate and analyze the accuracy of the Simonetti adherence score among patients on chronic use of vitamin K antagonists and their time in therapeutic range (TTR) of the international normalized ratio as a measure of quality of anticoagulation. A prospective cohort study with a nonrandomized intervention in patients from an anticoagulation center of a public hospital. Baseline data were collected from May to September 2017, and follow-up data were obtained eight months after a nurse-led  educational intervention, which was given to all patients after consent form and after applying the adherence score (N=205). The intervention was undertaken through 30-40 min conversation about relevant factors that had been previously identified in the score derivation study, which comprised drug-drug interactions, inadequate OAC use, comorbidities, effects of food on vitamin K absorption, and invasive procedures. A receiver operating characteristic (ROC) curve was applied to validate the adherence score in terms of prediction of INR out of recommended therapeutic range. At baseline, mean adherence score was 44.69 and standard deviation (SD) was 18.37, and   mean TTR was 41.07 (SD 15.40). Patients were reassessed after   8 months. At follow-up, there were significant improvements in mean adherence score 54.28 (SD 13.13), and in mean TTR 50.99 (SD 26.10). The Simonetti adherence score yielded high performance and accuracy in clinical practice among patients on chronic use of vitamin K antagonists. Our data indicate that nurse led educational intervention yielded favorable impact in terms of adherence score and TTR improvements.